2018
DOI: 10.1097/pts.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

Applying Intelligent Algorithms to Automate the Identification of Error Factors

Abstract: Objectives: Medical errors are the manifestation of the defects occurring in medical processes. Extracting and identifying defects as medical error factors from these processes are an effective approach to prevent medical errors. However, it is a difficult and time-consuming task and requires an analyst with a professional medical background. The issues of identifying a method to extract medical error factors and reduce the extraction difficulty need to be resolved. Methods:In this research, a systematic metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Mathematical/text data To identify, extract, and minimize medical error factors in the medication administration process Jin et al [37] Machine-learning algorithms identified error rates in imaging, lab, and medication orders…”
Section: Patients and Healthy Participantsmentioning
confidence: 99%
“…Mathematical/text data To identify, extract, and minimize medical error factors in the medication administration process Jin et al [37] Machine-learning algorithms identified error rates in imaging, lab, and medication orders…”
Section: Patients and Healthy Participantsmentioning
confidence: 99%
“…3,18 MAE is the deviation between the medication content pre-provided to nurses in the medication operation and the actual medication content. 16…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the complexity and diversity of medical errors make it impossible to generalize them, and each type must be categorized and discussed in depth. 10,16,17 There are many types of medical errors, including MAEs, falls, blood collection and transfusion errors, and surgical errors, with MAEs accounting for a relatively high proportion at more than 50% of overall medical errors during medication nursing delivery. 3,18 MAE is the deviation between the medication content pre-provided to nurses in the medication operation and the actual medication content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 Due to the diversity, urgency, complexity, and variability of medical procedures, there is a large amount of information processing content and associated cognitive processes involved in the daily operations of medical staff, which easily causes mental fatigue. 14 , 15 Mental fatigue is defined as a psychobiological state caused by long-term and/or intense cognitively demanding activities, and is characterized by subjective feelings of “tiredness” and “lack of energy”. 16 In the medical field, mental fatigue is the primary manifestation of fatigue.…”
Section: Introductionmentioning
confidence: 99%